Antibiogram for Haemodialysis Catheter-Related Bloodstream Infections - Abdul Halim Abdul Gafor; Pau Cheong Ping; Anis Farahanum Zainal Abidin; Muhammad Zulhilmie Saruddin; Ng Kah Yan; Siti Qania’ah Adam; Ramliza Ramli; Anita Sulong; Petrick Periyasamy (International Journal of Nephrology)
Background. Haemodialysis (HD) catheter-related bloodstream infections (CRBSIs) are a major complication of long-term catheter use in HD. This study identified the epidemiology of HD CRBSIs and to aid in the choice of empiric antibiotics therapy given to patients with HD CRBSIs. Methods. Patients with HD CRBSIs were identified. Their blood cultures were performed according to standard sterile technique. Specimens were sent to the microbiology lab for culture and sensitivity testing. Results were tabulated in antibiograms. Results. 18 patients with a median age of 61.0 years (IQR: 51.5–73.25) were confirmed to have HD CRBSIs based on our study criteria. Eight (44.4%) patients had gram-negative infections, 7 (38.9%) patients gram-positive infections, and 3 (16.7%) patients had polymicrobial infections. We noted that most of the gram-negative bacteria were sensitive to ceftazidime. Unfortunately, cloxacillin resistance was high among gram-positive organisms. Coagulase-negative Staphylococcus and Bacillus sp. were the most common gram-positive organisms and they were sensitive to vancomycin. Conclusion. Our study revealed the increased incidence of gram-negative organism in HD CRBSIs. Antibiogram is an important tool in deciding empirical antibiotics for HD CRBSIs. Tailoring your antibiotics accordingly to the antibiogram can increase the chance of successful treatment and prevent the emergence of bacterial resistance.